Relevance between the degree of industrial competition and fair value information: Study on the listed companies in China - Xuemin Zhuang; Yonggen Luo (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The purpose of this article is to study whether there exists natural relationship between fair value and corporate external market. A series of special phenomenon in the application of fair value arouses our research interests, which present evidences on how competition affects the correlation of fair value information. Design/methodology/approach: this thesis chooses fair value changes gains and losses and calculate the ratio of DFVPSit as the alternative variable of the fair value. In order to effectively inspect the mutual influence between the degree of industry competition and the value relevance of fair value, and reduce the impact of multi-collinearity, we built a regression model on the hypothesis, which supposes that if other conditions are the same, the fair value information has greater value relevance if the degree of the industry competition is greater. To test the hypothesis, we use the comparison of the DFVPSit coefficient absolute value to judge the value relevance of fair value information, and the greater the absolute value is, the higher relevance between the changes in fair value per share profits and losses with the stock prices. Findings: The higher the degree of competition in the industry is, the more fair value information relevance is. Also, there are evidences representing that fair value information often presents negative correlation with the stock price. Originality/value: The main contribution of the article is to show that not only need we make the formulation and implementation of the high quality of fair value accounting standards to suit for both the national conditions and international practice, but also need we further to improve the company's external governance mechanism to promote fair value's information correlation.
Keywords: 650; fair value information quality; value relevance; industry competition